China: Reforming the Gaokao - Postiglione, Gerard A (International Higher Education, 2014)
China’s newest reform of the gaokao will split the exam into two modes, one aiming at technically inclined students and the other at the traditionally academically oriented students. Six hundred local level colleges are asked to restructure their teaching programs from academic education to applied technology and professional education. Success of the reform will hinge on the quality of the education provided by the colleges, reducing the current level of graduate unemployment, up scaling the nation’s industrial production, and raising the social status of a technical-professional education.